Luteolin inhibits triple-negative breast cancer by inducing apoptosis and autophagy through SGK1-FOXO3a-BNIP3 signaling - Wu, Ling; Lin, Yingda; Gao, Songyu; Wang, Yongfang; Pan, Huiji; Wang, Zhaozhi; Pozzolini, Marina; Yang, Fengling; Zhang, Haiyan; Yang, Yi; Xiao, Liang; Xu, Yuan (Frontiers in Pharmacology, 2023)
Triple-negative breast cancer (TNBC) is one of the most prominent neoplasm disorders and lacks efficacious treatments yet. Luteolin (3’,4’,5,7-tetrahydroxyflavone), a natural flavonoid commonly presented in plants, has been reported to delay the progression of TNBC. However, the precise mechanism is still elusive. We aimed to elucidate the inhibition and molecular regulation mechanism of luteolin on TNBC.The effects of luteolin on the biological functions of TNBC cells were firstly evaluated by cell counting kit-8 assay, flow cytometry, wound-healing assay, and transwell migration assay, respectively. The mechanism of luteolin on TNBC cells was then analyzed by RNA sequencing and verified by RT-qPCR, Western blot, transmission electron microscopy, etc. Finally, in vivo mouse tumor models were constructed to further comfirm the effects of luteolin on TNBC.Luteolin significantly suppressed cell proliferation, invasion, and migration, and promoted cell apoptosis in a dose- and time-dependent manner. In TNBC cells treated with luteolin, SGK1 and AKT3 were significantly downregulated while their downstream gene BNIP3 was upregulated. According to the results of 3D modeling, the direct binding of luteolin to SGK1 was superior to that of AKT3. The inhibition of SGK1 promoted FOXO3a translocation into the nucleus and led to the transcription of BNIP3 both in vitro and in vivo, eventually facilitating the interaction between BNIP3 and apoptosis and autophagy protein. Furthermore, the upregulation of SGK1, induced by luteolin, attenuated the apoptosis and autophagy of the TNBC. Luteolin inhibits TNBC by inducing apoptosis and autophagy through SGK1-FOXO3a-BNIP3 signaling.